2015
DOI: 10.1002/2015wr017658
|View full text |Cite
|
Sign up to set email alerts
|

Steady nonuniform shallow flow within emergent vegetation

Abstract: Surface flow redistribution on flat ground from crusted bare soil to vegetated patches following intense rainfall events elevates plant available water above that provided by rainfall. The significance of this surface water redistribution to sustaining vegetation in arid and semiarid regions is undisputed. What is disputed is the quantity and spatial distribution of the redistributed water. In ecohydrological models, such nonuniform flows are described using the Saint-Venant equation (SVE) subject to a Manning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 59 publications
10
67
1
Order By: Relevance
“…They suggested that drag coefficient must be varying along vegetation length in stream-wise direction. Their finding illustrated that C d (x)/< C d > increases and then decreases with increasing distant from flume inlet forming a hump-shape that has been studied elsewhere [28]. The drag coefficient for dense vegetation differs from that of single vegetation of the same form.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…They suggested that drag coefficient must be varying along vegetation length in stream-wise direction. Their finding illustrated that C d (x)/< C d > increases and then decreases with increasing distant from flume inlet forming a hump-shape that has been studied elsewhere [28]. The drag coefficient for dense vegetation differs from that of single vegetation of the same form.…”
Section: Introductionmentioning
confidence: 62%
“…Most of the studies used solid circular cylinders in regular rows for quantifying the impact of vegetation on flow characteristics and drag coefficient [28][29][30][31][32][33]. However, cylinders do not adequately represent vegetation because of the differences in flexibility, roughness, shape, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, overland flow of water during intense rainfall events on semi-arid flat plains is the subject of ongoing research (e.g. [89,96,72]). A detailed description of the overland water flow and infiltration into the soil that occurs before water is consumed by plants relies on a clear distinction between the surface water density and the soil moisture.…”
Section: Discussionmentioning
confidence: 99%
“…For an isolated cylinder, the local C d (labeled as C d ,iso ) can be determined from the bulk velocity and rod diameter by forming an element Reynolds number Re d = UD / ν . An approximate expression for C d ,iso that describes data for isolated cylinders and for Re d < 10 5 is given by (Cheng, ; Wang et al, ) Cd,iso=11false(Redfalse)0.75+0.9Γ1()Red+1.2Γ2()Red, where Γ1()Red=1exp()1000Red and Γ2()Red=1exp[]()Red45000.7. …”
Section: Theorymentioning
confidence: 99%
“…A number of formulations have been proposed to link S f to vegetation drag coefficient C d assuming a steady uniform flow. These formulations, or variants on them, have been shown to capture blockage, sheltering, angle of separation, among others (Baptist et al, ; Carollo et al, ; Chapman et al, ; Cheng, ; Cheng & Nguyen, ; Dijkstra & Uittenbogaard, ; Etminan et al, ; James et al, ; Järvelä, ; Kouwen et al, ; Kim et al, ; Konings et al, ; Tanino & Nepf, ; Wang et al, , ; Zhao et al, ). However, the dam break problem leads to transient surface waves (Kobayashi et al, ) as well as large horizontal gradients in Froude numbers (Ishikawa et al, ) not present in conventional uniform canopy flow studies.…”
Section: Introductionmentioning
confidence: 99%